The answer is: 110/3 = 36 ⅔ ; or, write as: 110/3 ; or, write as 36.66666667;
__________________________
Explanation: (Two methods):
_____________________________________________
Method 1):
____________
Since: "(1/3)x" and "7x" are "like terms" , add them together, to get:
____________________________________________________
"(7 + 1/3)x "
________________
→ 7 = 7/1 = ?/3 ; → (7*3)/ (1*3) = 21/3;
→ 7 = 21/3 ;
→ 7 1/3 = 7 + 1/3 = 21/3 + 1/3 = 22/3;
→ (7 1/3)x = (22/3) x
→ We have: "(22/3)x" ; x = 5 ;
→ So substitute the "5" for "x"; and solve the expression:
→ (22/3)x = (22/3)*5 = (22*5) / (3*1) = 110/3 = 36 ⅔
____________
Method 2):
________________________________________
Either: 1):
__________________________________
Given: (1/3)x + 7x ; x = 5; Solve for "x" .
_____________________________________________
→ Substitute the given value, "5", for "x"; to solve the expression:
____________________________
→ (1/3)*5 + 7* 5 = (5/3) + 35 = 1 ⅔ + 35 = 36 ⅔ ; or write as "110/3"; or, write as: 36.66667.
___________________
Or: 2):
_____________________________________
Given: (1/3)x + 7x ; x = 5; Solve for "x" .
_____________________________________________
→ Substitute the given value, "5", for "x"; to solve the expression:
Given: (1/3)x + 7x ; x = 5; Solve for "x" .
→{Note: Similar to, a bit different from, the above method):
_____________________________________________
→Here is what is done differently:
→ (1/3)x + 7x → = (x/3) + 7x) ;
_______________________________
Now, we have:
_______________________________
→ (x/3) + 7x ; x = 5; → Plug in the value, "5" for the "x" values:
_______________________________
→ (5/3) + (7*5) = (5/3) + 35 = 1 ⅔ + 35 = 36 ⅔ ; or write as "110/3"; or, write as: 36.66667.
_________________________________